Analisis Kualitas Butir Soal Pilihan Ganda Tema 7 Indahnya Keragaman di Negeriku Kelas IV Madrasah Ibtidaiyyah - Nurjanah, Maya; Istiningsih, Istiningsih; Mangkuwibawa, Hilman (Jurnal Paedagogy, 2022)
The purpose of this study was to analyze the level of quality of the questions consisting of the level of difficulty, discriminatory power of questions, validity of items, and reliability on Theme 7 The Beauty of Diversity in My Country. This study uses a quantitative descriptive research method. The research was conducted at MI Al-Khoiriyyah, especially in class IV using 10 multiple choice questions. Collecting data in this study using interviews and documentation. The data analysis technique uses the SPSS application as the data calculation. The results of this study indicate that the questions used are reliable or stable and feasible to be given to students. This is reinforced by the results of the analysis which show that for the level of difficulty there are 9 questions in the medium category and one question in the easy category. For PE power, there is only one question with a bad category, 3 questions in the medium category and the remaining 6 questions in the good category. Regarding validity, there are two questions that are not valid, and in vain, there are 8 valid questions. The reliability test of the data has a high correlation with R1 = 1.00 which means the questions are said to be reliable or the results are relatively stable and reliable.